Wisdom and folly in Euripides - Kyriakou, Poulheria; Rengakos, Antonios (Trends in classics. Supplementary volumes ;, 2016)
"The volume throws fresh light on a major polarity in Euripidean drama, including its roots in the tradition and its reception in vase-painting and literature. Virtually all Euripidean characters are subject to folly and claim some measure of wisdom. Leading international scholars discuss the polarity and the plays' ambiguities from various angles and theoretical perspectives, offering trenchant insights into moral, social and historical issues."--